Analisis Faktor yang Mempengaruhi Kurangnya Minat Masyarakat dalam Menabung di Bank Sumut Kcp Syariah Kota Baru Marelan - Khairussyifa, Salwa; Jannah, Nurul (Medan Resource Center, 2022)
This research is motivated by how the banking sector attracts customers and retains them so that companies can develop is the main problem faced by Islamic financial institutions such as Islamic banks. Meanwhile, the people of the city of Baru Marelan are less interested in saving at Islamic banks due to several factors. The purpose of this study is to determine whether or not there is an influence of knowledge, service, location, and product factors on the lack of public interest in saving in Islamic banks and how much influence this has on the lack of interest of the people of the new city of Marelan. Saving in Islamic Banks.The research method used in this research is quantitative with multiple linear regression analysis as an analytical tool. By proving the hypothesis used with a significant test. The sample in this study were respondents. The independent variable in this study is the lack of public interest, this research was conducted on the community in Kota Baru Marelan.Based on regression analysis at a significant rate of 5%, it shows that the knowledge and product variables have a significant influence on the lack of public interest in saving. The results of the F test for the variable lack of public interest in saving can be influenced by the knowledge and product variables together. Partially, knowledge and products have a significant effect on the lack of public interest. Location and service have no significant effect on the lack of interest in the people of Kota Baru Marelan in saving at Islamic Banks. While the most dominant influence is on the variable (X), where the beta value of 0.620 is greater than the other independent variables.